The Correlation of Education Service Quality and Alumni Satisfaction: A Case Study in Islamic Higher Education - Fauzi Muharom; Lihar Raudina Izzati; Dwi Purbowati; Erlinda Rahma Dewi (Mudir : Jurnal Manajemen Pendidikan, 2023)
Universities must be able to provide good quality education and explore all aspects of excellent service in order to improve the image of tertiary institutions to face competitive competition. In this study, the stakeholders in question are external stakeholders, namely alumni. Some of the educational services that will be discussed in this study are leadership at the faculty and study program level, learning processes carried out by lecturers, educational services carried out by employees or staff or educational staff, facilities and infrastructure or facilities obtained by students, as well as alumni institutions accommodate alumni. This study aims to determine whether there is an influence from the quality of educational services in one of the Islamic tertiary institutions on alumni satisfaction and how much the influence is. The population in this study were alumni of the State Islamic Institute (IAIN) Surakarta. The research sample was 300 people. The results of this study are that there is a relationship between leadership in faculties and study programs, learning processes, administrative services, facilities and infrastructure, and alumni organizations as a whole with the level of alumni satisfaction simultaneously or jointly having a positive and strong relationship to the level of alumni satisfaction of 57.7%, while 42.3% is determined by other factors.